The Effect of Storage Time on The Quality of Duck Eggs in The Highlands of Bedugul - S. G., Wayau; Wiyana, I K. A.; Wijana, I W. (Jurnal Peternakan Tropika, 2019)
Research to determine the external and internal quality of duck eggs stored in the highlands of Bedugul for 35 days. This research was conducted in Bedugul area, Tabanan Regency, Bali, while egg-breaking and data collection were carried out at the Poultry Laboratory of the Faculty of Animal Science, Udayana University for 6 weeks. The Completely Randomized Design (CRD) was applied in this research, consisting of 6 treatments namely eggs without being stored as a control (P0), egg storage for 7 days (P7), egg storage for 14 days (P14), egg storage for 21 days (P21), egg storage for 28 days (P28), and egg storage for 35 days (P35). Three replication was given for each treatment and 5 duck eggs were used in each replication. The external quality variables observed were the index of egg shape and egg weight. Whereas the internal quality variables were eggshell thickness, egg yolk color, haugh unit (HU), and egg pH. The experiment results showed that different storage times statistically gave significantly difference (P<0.05) for eggshell thickness, egg yolk color, haugh unit, and egg pH variables. Meanwhile variables of egg shape index and egg storage weight of 7 days to 35 days gave no significant difference (P> 0.05). It was concluded that the storage of duck eggs in the Bedugul highlands with temperatures of 16 o C - 24 0 C and with 68-90% dampness, did not reduce the external quality which includes egg weight and egg shape index, but did affect the internal quality of duck eggs. Reduction of duck egg haugh units began to occur at 7 days storage, while storage for 14, 21, 28 and 35 days decreased the thickness of eggshell, egg yolk color, and increased egg pH. The result of the assessment of the grade of duck eggs based on the value of the haugh unit obtained grade A so that the quality of duck eggs can be categorized still good.   Keywords : Duck Eggs, Storage Time, Quality Of Duck Eggs